2004
DOI: 10.1111/j.1398-9995.2004.00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxins in asthma: potential therapeutic mediators on bronchial inflammation?

Abstract: Arachidonic acid metabolism represents an important source of mediators with ambivalent actions. Among these, lipoxins (LXs) are the first agents identified and recognized as anti-inflammatory endogenous lipid mediators, which are involved in the resolution of inflammation and are present in the airways of asthmatic patients. Lipoxins result mainly from the interaction between 5 and 15-lipoxygenases (LO) and their levels are modulated by the degree of bronchial inflammation as well as by the long-term glucocor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 145 publications
(175 reference statements)
1
18
0
Order By: Relevance
“…LXA4 and ANXA1 are mediators which have anti-inflammatory effects [12,17]. In human studies, it has been shown that the level of LXA4 is low in severe asthma [9,10,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LXA4 and ANXA1 are mediators which have anti-inflammatory effects [12,17]. In human studies, it has been shown that the level of LXA4 is low in severe asthma [9,10,18].…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is one of the most important chronic inflammatory diseases, characterized by variable airflow obstruction and airway hyperresponsiveness in childhood. A large number of mediators that affect the airways play a role in the pathogenesis of asthma [3]. Lipoxins are the first agents determined to be anti-inflammatory endogenous lipid mediators involved in the resolution of inflammation [4].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the endogenous lipoxin isomer, the LXA 4 (5S,6R,15S-trihydroxy-7,9,13-trans-11-cis-eicosatetraenoic acid), have been reported on leukocyte trafficking via modulation of chemotaxis, adhesion, transmigration, and phagocytic clearance of apoptotic cells (13,20,39). In airway epithelial cells, since the first detection of LXA 4 in bronchoalveolar lavage in 1990, an anomalous low production of LXA 4 has been reported in airway of cystic fibrosis (CF) and severe asthmatic patients, which could explain the persistent inflammation in these severe airway diseases (6,8,24,29,49). In a previous study, we have shown that airway epithelial cells are a biological target for LXA 4 .…”
mentioning
confidence: 97%
“…They are synthesized at inflammation sites, and their anti-inflammatory properties have been widely reported (4,31,34,44). The effects of the endogenous lipoxin isomer, the LXA 4 (5S,6R,15S-trihydroxy-7,9,13-trans-11-cis-eicosatetraenoic acid), have been reported on leukocyte trafficking via modulation of chemotaxis, adhesion, transmigration, and phagocytic clearance of apoptotic cells (13,20,39).…”
mentioning
confidence: 99%
“…Lipoxins are eicosanoids formed by lipoxygenases from arachidonic acid and play a key role in the resolution of inflammation (2,6,19,41). In addition, lipoxin A 4 (LXA 4 ) has been reported to have other functions such as regulation of airway epithelial ion transport and airway surface liquid layer dynamics in CF (4,15,46).…”
mentioning
confidence: 99%